Anatomic Dissection Tractography: A New Method for Precise MR Localization of White Matter Tracts - Kier, E. Leon; Staib, Lawrence H.; Davis, Lawrence M.; Bronen, Richard A. (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: Several white matter tracts in the brain cannot be identified on MR studies because they are indistinguishable from the surrounding white matter. We sought to develop a method to precisely localize white matter tracts by correlating anatomic dissections with corresponding MR images.METHODS: MR imaging was used to guide anatomic dissection of the uncinate fasciculus. Formalin-preserved brains were imaged before and after several stages of dissection. Progressive dissection was guided by using volume-rendered and cross-sectional images of the dissected specimens. To precisely define the location of a tract, its surface was traced on the corresponding three-dimensional MR image of the dissected specimen. MR images of the dissected and intact specimens were coregistered to allow the tracings to be projected onto multiplanar reformatted images of the intact specimen.RESULTS: The uncinate fasciculus in the anterior temporal lobe and external and extreme capsules was dissected without destroying adjacent structures. Coregistration of the MR images from intact and dissected specimens permitted precise MR identification of the surface of this tract. These methods were successful for two additional tracts. (The dissected anatomy, MR anatomy, and clinical examples of the three tracts are described in a companion article.)CONCLUSION: MR-assisted anatomic dissection permits limited removal of brain tissue so that important anatomic and surgical relationships can be demonstrated on correlated MR studies. This method can be applied to other white matter tracts that are indistinguishable on MR studies and to situations in which anatomic validation of normal and abnormal diffusion tractographic studies is needed.